(untitled) (Sociologisk Forskning, 1999)
This study focuses on social relations in school classes and their importance for mental well-being in middle childhood. The aspect of social relations under study is the status relations in the school class and both the individual’s own status position and the status distribution of the school class as a whole was considered. The number of children analysed was 13,932 and the number of school classes 524. The results show a clear association at individual level: the higher the status position the more uncommon is malaise. This is true both when malaise is reported by the teacher and by a parent, for both boys and girls and irrespective of the number of friends. The association was also generally present within school. It exists regardless of grade, type of school and class size. Furthermore, a minority of the classes did not contain any outsiders and here malaise was less common in all status positions. Consequently, that some children are put outside the group indicates problematic conditions for the persons in question but also for the other group members.